Influence of Heat Treatment on the Corrosion of Microalloyed Steel in Sodium Chloride Solution - Asiful Hossain Seikh (Journal of Chemistry)
Microalloyed Steels find wide application in car bodies and other engineering parts because of its high strength as well as high ductility. Very fine grained microstructure is the reason behind the combination of strength and ductility. It has been reported that repeated quenching leads to further refining of microstructure. In the present investigation, corrosion resistance property of E34 microalloy steel has been studied in 3.5% NaCl solution in different microstructural conditions such as the as rolled one and three repeated quenched conditions. Weight loss, potentiodynamic polarization method, and electrochemical impedance spectroscopy (EIS) techniques have been used. To reveal the corrosion resistance of different treated steels, some significant characterization parameters such as Ecorr, Icorr, Rp, and Rct in linear polarization and EIS curves were analyzed and compared. It is found that with repeated recrystallization grains become finer, and corrosion rate increases suggesting that a compromise has to strike between high mechanical property and corrosion rate.